Determining static stiffness of damper elastic rings - D. S. Diligensky; D. K. Novikov; K. V. Boyarov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2022)
The article describes a method for experimental evaluation of the stiffness of an elastic damper ring. A thin-walled low-stiffness ring with uniformly distributed smooth protrusions on the inner and outer surfaces acts as a damper ring. Despite the widespread use of such a design in domestic and foreign mechanical engineering, control of the characteristics of this element and, accordingly, of the support as a whole remains quite difficult. A numerical model was developed, the reliability of which is confirmed by analytical calculations. To check the data obtained by numerical calculations, a special device was designed, which was installed on the galdabini tensile testing machine, where a series of measurements was carried out. Analysis of the data obtained showed a significant difference between the numerical, analytical and experimental data, which can be explained by the discrepancy between the equipment used and the boundary conditions of the theoretical model. The parameters of the device were selected in such a way that its rigidity was much higher than the rigidity of the elastic ring under study. The paper describes the improvement of both the design of the device and the method for determining the stiffness of the elastic ring of the damper using the specified measuring equipment. After making corrections, the obtained data on the scatter of the stiffness of the elastic ring are in good agreement with the analytical and numerical dependence, which makes it possible to use the data of the latter to refine the analytical methods in the future